Prevalência de Pré-Diabetes e Fatores de Risco Cardiovascular na Guarnição do Exército de Santa Maria – RS - Neves, Matheus da Cunha Goggia (2020)
Introduction: Countless studies have shown that cardiovascular disease represents the main cause of death in the world population and that glycemic alteration is a clinical condition significantly associated with increased morbidity and mortality. Several factors have been associated with these conditions, including poor eating habits and a sedentary lifestyle. It appears that these outcomes have been affecting the younger population, even the Brazilian military. Objective: To investigate the prevalence of dysglycemia and its relationship with the risk factors associated with cardiovascular risk in the Brazilian Army military. Methodology: Cross-sectional study involving 230 military personnel stationed in Military Organizations of the Brazilian Army of Rio Grande do Sul, from July to November 2019. Data collection occurred through a socio-demographic questionnaire, anthropometric assessment and analysis of electronic medical records for data collection. biochemical exam data. Dysglycemia was classified according to the Guidelines of the Brazilian Diabetes Society 2019-2020. The Framinghan Score was used to identify the risk of developing cardiovascular disease over 10 years, based on the criteria used by the Ministry of Health. The statistical analysis included the Kolmogorov-Smirnov Test, Student's T Tests, Mann-Whitney, ANOVA, Kruskal Wallis with Dunn's Post Hoc, Pearson's Chi-square test, Fischer's Exact Test, Spearman's Correlation Test and the Poisson regression model. The analyzes were conducted using SPSS for Windows version 21.0 and p <0.05 was considered significant. Results: The average age of the participants was 35 (8) years. Of these, 17% had dysglycemia and they were older (P = 0.001), lived in their own home (P = 0.040), had a greater number of children (P = 0.004) and more time in the military (P = 0.001). The measurement of dysglycemic glycemia was higher (105.2mg / dL vs. 82.1mg / dL) when compared to normoglycemic (P <0.001) and these had a higher percentage of cardiovascular risk, according to the Framingham Risk Score (P = 0.011). The risk of CVD was observed in those who had WC (P = 0.016), WC (P = 0.023), and WHR (P <0.001) above the desired level, used antihypertensive drugs (P <0.001), did not practice physical activity (P = 0.006) and with high triglycerides (P <0.001). The correlation was low with SBP, DBP, weight, triglycerides, WC and number of children and moderate when correlated with age, WHR, income, WC and military activity time (P <0.001). In this study, no correlation was found between dysglycemia and the risk of developing cardiovascular disease. Conclusion: The results of this study demonstrate a high prevalence of dysglycemia in the military population and there is no association between this change and the risk of cardiovascular disease in the military. In addition, in the general findings, we identified that most of the sample is healthy and presents a low risk for the development of cardiovascular diseases over 10 years. However, it is essential to implement strategies for disease prevention and health promotion in specific population groups where the prevalence of obesity, diabetes, dyslipidemia and cardiovascular diseases are present.